(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the limitations of criminal law in making the identity of a criminal go viral, as well as the synchronization between the Electronic Information and Transactions Law (UU ITE) and the Personal Data Protection Law (UU PDP). The study uses a normative juridical method with a statute approach and a conceptual approach. The research data consists of primary, secondary, and tertiary legal materials collected through library research. Data analysis was conducted using descriptive qualitative methods using deductive legal reasoning to examine the relationship between personal data protection norms and public participation in law enforcement. The results show that the act of making the identity of a criminal go viral can be qualified as doxing if it is done with an intentional element (mens rea) to damage a person’s dignity or disseminate personal data without authorization. Legal limitations require society to respect the principle of the presumption of innocence, the protection of permanent digital traces, and digital ethics in the use of social media. The synchronization between the ITE Law and the PDP Law forms a complementary legal framework, where legal certainty is achieved when public participation is channeled through official reporting mechanisms to law enforcement officials. This study’s limitation lies in the use of a normative approach that has not examined empirical implementation in the field. Therefore, further research is recommended to use an empirical approach to evaluate the effectiveness of the ITE Law and the PDP Law in addressing doxing practices and digital vigilantism.